2001
DOI: 10.1001/archpedi.155.11.1238
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Violence and Associated Health-Risk Behaviors Among Adolescent Girls

Abstract: Adolescents exposed to violence are at increased risk of multiple adverse health behaviors. Programs designed to improve health outcomes should target this high-risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
99
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(112 citation statements)
references
References 25 publications
11
99
1
1
Order By: Relevance
“…Findings indicated that community violence exposure was significantly associated with drug and sexual risk behaviors among detained youth. These findings corroborate those of other studies utilizing community-based samples of youth (Berenson, Wiemann, & McCombs, 2001;Stiffman, Dore, Cunningham, & Earls, 1995;Voisin, 2003Voisin, , 2005. Taken together, these results suggest the need to develop better assessment instruments to identify youth who are exposed to both community violence and engage in drug and sexual risk behaviors.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Findings indicated that community violence exposure was significantly associated with drug and sexual risk behaviors among detained youth. These findings corroborate those of other studies utilizing community-based samples of youth (Berenson, Wiemann, & McCombs, 2001;Stiffman, Dore, Cunningham, & Earls, 1995;Voisin, 2003Voisin, , 2005. Taken together, these results suggest the need to develop better assessment instruments to identify youth who are exposed to both community violence and engage in drug and sexual risk behaviors.…”
Section: Discussionsupporting
confidence: 88%
“…Collectively, these studies document that youth who are exposed to high rates of violence within their communities are at greater risk for engaging in behaviors such as illicit drug use and unsafe sexual behaviors (Berenson, Wiemann, & McCombs, 2001;Stiffman, Dore, Cunningham, & Earls, 1995;Voisin, 2003Voisin, , 2005. However, the pathways which mediate such relationships are not adequately understood or empirically researched.…”
Section: Introductionmentioning
confidence: 99%
“…Some prior literature focuses on issues such as STDs, HIV and other public health issues, and consistently finds strong associations [8][9][10]. A few studies measure particular acute and rare effects-such as poisonings, overdoses, intense intoxication [11].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies on the prevalence of medical conditions in adolescents with alcohol and drug misuse or problems has largely been conducted on public populations [9], inpatient populations [5] or general populations [13,25]. Other studies use small samples, case studies of one or few patients, have no or very small non-substance-using comparison groups [12,17,19,22,26,27] rely solely on self-report of medical problems [12,13] or overall health status [6,28], or do not examine specific medical conditions [7].…”
Section: Introductionmentioning
confidence: 99%
“…There is also a well-documented link between NSSI and eating disorders (Favazza et al, 1989;Favaro and Santonastaso, 2000;Wonderlich, 2001;Dohm, 2002;Paul, 2002;Sansone and Levitt, 2002;Stein et al, 2004; but see also Zlotnick et al, 1999). Rates of self-injury are also elevated six-fold in people who have been exposed to physical acts of violence or threats to their lives (Berenson et al, 2001). There is also evidence linking risky sexual practices in adolescents with self-injurious behaviors such as cutting (DiClemente et al, 1991;Brown et al, 2005;Brown et al, 2008).…”
mentioning
confidence: 99%